THE NEED TO IMPROVE SOCIAL EMOTIONAL COMPETENCES IN THE TRAINING OF FUTURE TEACHERS: STUDENTS' ATTITUDES - Braslauskienė, Rasa; Klanienė, Ilona; Lengvinas, Donatas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Today, scholars raise the need for the development/self-development of social emotional competences in schools and emphasize the importance of its development for successful socialization of children. Scientific articles emphasize the importance of improving teachers' social emotional competences for social emotional education of children. The need to improve social emotional competences is underlined in Lithuanian and European Union documents that point to the importance of high-quality social emotional education and the need to improve teachers' competences. Recently, researches have been focusing mainly on the peculiarities of children's social emotional education, yet the problem of improving social emotional competences of pedagogues is left aside. The article reveals the attitude of students of the Childhood pedagogy study programme towards the existing social emotional competences and substantiates the need for its improvement in the education of future pedagogues. Findings of qualitative research (individual interview with the students) are presented. The results of the study have revealed that students do not always succeed in recognizing and managing the feelings that emerge, especially they lack knowledge and skills to control stressful situations. The analysis of students' perspective highlighted the need for the improvement of social emotional competences in the education of future pedagogues.